Mudflat Ecology (Aquatic Ecology Series ;, 2018)
Intertidal mudflats are distinct, highly-productive marine habitats which provide important ecosystem services to the land-sea interface. In contrast to other marine habitats, and despite a large body of primary scientific literature, no comprehensive synthesis exists, such that the scattered knowledge base lacks an integrated conceptual framework. We attempt to provide this synthesis by pulling together and contextualizing the different disciplines, tools, and approaches used in the study of intertidal mudflats. The editor pays particular attention to relationships between the various components of the synthesis, both at the conceptual and the operational levels, validating these relationships through close interaction with the various authors.